Space-to-ground infrared camouflage with radiative heat dissipation - Bing Qin; Huanzheng Zhu; Rongxuan Zhu; Meng Zhao; Min Qiu; Qiang Li (Light: Science & Applications)
Abstract With the development of space exploration and exploitation, it is imperative to address the potential threats posed to space objects, particularly ground-based infrared observation. However, in the extreme space environment, achieving infrared camouflage across different bands with simultaneous thermal management is challenging and has so far slipped out of concern. Here, we propose the space-to-ground infrared camouflage strategy, compatible with radiative heat dissipation. Camouflage in the H, K, mid-wave-infrared (MWIR), and long-wave-infrared (LWIR) bands is achieved through a multilayer structure, with radiative heat dissipation in the very-long-wave-infrared (VLWIR) band. High absorptivity (0.839/0.633) in the H/K bands minimizes the reflected signal of solar radiation and low emissivity (0.132/0.142) in the MWIR/LWIR bands suppresses the thermal radiation signal. Additionally, high emissivity (0.798) in the VLWIR band ensures efficient thermal management, resulting in a temperature decrement of 39.8 °C to the metal reference in the simulated space environment (with 1200 W m− 2 thermal input). This work inspires sophisticated spectral manipulation in extreme environments and guides the development of camouflage and radiative heat dissipation techniques for space objects.